Legal Protection of NFT Digital Objects by NFT Marketplace Based on Comparison with Domain Names - Kirana, Nabilah Putri (Jurnal Cakrawala Hukum, 2023)
Advances in information technology have driven economic globalization. The interests protected by such are no longer only its products but also its intellectual property rights. One form of utilizing digital technology and the internet in the economic field for two-dimensional artworks is through Non-Fungible Tokens (NFTs). NFT is a form of digital asset in the field of art, where usually transactions that occur are carried out on a special platform. This article examines the protection of the creator’s exclusive rights from the tokenization of his work by other parties as well as the responsibilities of the NFT Marketplace. Normative analytical and juridical descriptive research methods are used for legal norms in copyright law related to the exclusive rights of creators and marketplace responsibilities for the commercialization of copyrighted works as NFTs based on these principles and theories. How to cite item: Kirana, Nabilah Putri, â€œLegal Protection of NFT Digital Objects by NFT Marketplace Based on Comparison with Domain Namesâ€ Jurnal Cakrawala Hukum 14 no. 3 (2023): 312-321. DOI: 10.26905/idjch.v14i3.11255.